Agriculture's contribution - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The next annual conference of the International Association of Agricultural Economists will look at reshaping agriculture s contribution to society, with sub-themes including environmental stewardship, efficiency in food and farming systems,...